PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN PELANGGAN MARUGAME UDON THE PARK SOLO - Nur Laili fauziah; Christiawan Hendratmoko (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This research examines how product quality, service quality, and price shape customer satisfaction at Marugame Udon The Park Solo. The study employs a quantitative design by distributing online questionnaires to customers who had visited the restaurant within the previous three months. A total of 80 valid responses were collected and analyzed using multiple linear regression techniques. The findings reveal that product quality significantly contributes to customer satisfaction, indicating that flavor consistency, freshness, and product presentation strongly influence customer experiences. Service quality also shows a positive and significant impact and emerges as the most influential factor, highlighting the importance of employee responsiveness, courtesy, and service efficiency. In contrast, price does not demonstrate a significant effect on customer satisfaction, suggesting that customers prioritize overall value rather than price considerations alone. Collectively, the results emphasize that superior product standards and excellent service performance are key drivers of satisfaction. These findings offer practical insights for restaurant managers to focus on service excellence and product consistency to maintain competitiveness in the increasingly dynamic culinary industry.